Eksplorasi Pengalaman Wisatawan dalam Wisata Daring ke Desa Batuan, Bali - Peni Zulandari Suroto; Made Handijaya Dewantara; Rizqa Tsania; Hanesman Alkhair; Bernadinus Realino Yudianto (Fakultas Seni Rupa dan Desain ITB, 2023)
Virtual tours are chosen as alternative tourism during the COVID-19 pandemic. This study aims to explore travelers’ experiences in their roles as participants in a virtual tour of Batuan Village, Bali. Qualitative approaches were used; interviews and focus group discussions (FGD) were conducted before the first alpha test (conceptualization of the virtual tour). The 2nd FGD was held to understand the feedback for improvement on the 2nd alpha test. Then, the 3rd FGD was used to explore inputs that can be applied by practitioners in organizing better virtual tours. Through descriptive analysis, six points related to experience are concluded: (1) an enjoyable experience from travelers, (2) an appreciation of the destination’s uniqueness, (3) a requirement of devices and platforms for a smooth virtual tour, (4) innovation to create a narrative story plot, (5) a bold character’s personification, and (6) a social media account to publish the tour information. The biggest challenges of this study were the web-app development and the virtual tour platform.